A syndrome of facial dysmorphism, cubital pterygium, short distal phalanges, swan neck deformity of fingers, and scoliosis. Issue 4 (23rd January 2014) - Girisha, Katta M.; Abdollahpour, Hengameh; Shah, Hitesh; Bhavani, Gandham SriLakshmi; Graham, John M.; Boggula, Vijay Raju; Phadke, Shubha R.; Kutsche, Kerstin
<x xml:space="preserve">Abstract</x> We report on an adolescent girl with sparse scalp hair, wide columella extending below alae nasi, webbing at elbows, broad finger tips, short distal phalanx of fingers, swan neck deformity of fingers, scoliosis, tall vertebrae, short fibulae, short fourth metatarsal bone, abnormal distal humeri, and unilateral clubfoot at birth. The combination of these features represents a novel phenotype. We sequenced the protein‐coding regions of the FLNA and FLNB genes and did not observe any pathogenic sequence variation. Chromosomal microarray revealed a de novo copy number variation of uncertain clinical significance on 7p22.3. © 2014 Wiley Periodicals, Inc.